Factors Associated with Antidepressant Effects of Ketamine: A Reanalysis of Double-Blind Randomized Placebo-Controlled Trial of Intravenous Ketamine for Treatment-Resistant Depression - Yonezawa, Kengo; Uchida, Hiroyuki; Yatomi, Taisuke; Ohtani, Yohei; Nomoto-Takahashi, Kie; Nakajima, Shinichiro; Mimura, Masaru; Tani, Hideaki (Pharmacopsychiatry, 2023)
Introduction Predictors of treatment response to intravenous ketamine remain unclear in patients with treatment-resistant depression (TRD); therefore, this study aimed to clarify these predictors using the US National Institutes of Health database of clinical trials.Methods Data from a placebo-controlled, double-blind, randomized controlled trial were used to assess the efficacy of intravenous ketamine in adult patients with TRD (NCT01920555). For the analysis, data were used from the participants who had received therapeutic doses of intravenous ketamine (i. e., 0.5 and 1.0 mg/kg). Logistic and multivariable regression analyses were conducted to explore the demographic and clinical factors associated with response to treatment or changes in the Hamilton Depression Rating Scale 6 items (HAM-D-6) total score.Results This study included 31 patients with TRD (13 women; mean±standard deviation age, 48.4±10.9 years). Logistic regression analysis showed that the age of onset was positively correlated with treatment response after three days of ketamine administration (β=0.08, p=0.037); however, no association was observed between treatment response and age, sex, baseline HAM-D-6 total score, or dissociative score assessed with the Clinician-Administered Dissociative States Scale 40 min after ketamine infusion. Multiple regression analysis showed that no factors were correlated significantly with the percentage change in the HAM-D-6 total score three days after ketamine administration.Discussion Later disease onset correlates with a better treatment response three days after ketamine infusion in patients with TRD. Glutamatergic signal transmission may be impaired in patients with an earlier onset of depression, resulting in decreased neuroplasticity, which diminishes ketamine response.
Keywords: depression; human; ketamine; treatment-resistant